Personal traits of physical education and sports professor according to the variable of professional experience and its reflection on social interaction among secondary stage pupils - thamene, boubaker; saker, tarek (sports creativity, 2025)
The study aimed to try to identify the degree of personality traits of the physical education and sports professor according to the variable of professional experience and its reflection on the social interaction of students in the secondary stage. The study was conducted consisting of (412) male and female students, and (15) professors from some secondary schools in the state of bejaia, who were chosen in a systematic, random manner, to using measures represented in: (the character traits measure for amani abdel wahab abdel maksoud 2017) consisting of four dimensions and (61) phrases, and the scale (the social interaction of Muhammad Nubian Muhammad ali 2010) consisting of four dimensions and (21) phrase, statistic processing was done using the package statistical social sciences (spss), where the results of the study were as follows: - the personality traits of the physical education and sports professor are affected by professional experience. - the levels of social interaction among students differ according to the degree of personality traits of the physical education and sports professo